EKSPLORASI GEOMETRI PADA DESAIN CANDI UNTOROYONO KLATEN MELALUI ETNOMATEMATIKA - Issabella, Anggun Silvia; Hadiprasetyo, Krisdianto (LPPM UNIMAL, 2025)
Mathematics and culture cannot be separated from each other in everyday life, because culture and mathematics are a whole unit and are used to solve everyday problems. The relationship between culture and mathematics is called ethnomathematics. The purpose of the research is to reveal the mathematical concepts contained, while the target is the shape of flat and spatial shapes. This research uses a qualitative method with an ethnographic approach. Data were obtained through direct observation, documentation, and image analysis. The identification of geometric shapes is done by analyzing the shape of buildings, such as flat and spatial shapes, to understand the mathematical concepts contained in the temple design. This study found that the design of Klaten Untoroyono Temple contains elements of geometry such as square, triangle, trapezoid, cube, block, and pyramid. These findings support ethnomathematics as an innovative and fun learning method to understand math concepts through culture.